UPAYA PENCEGAHAN TINDAK PERUNDUNGAN (BULLYING) MELALUI PROGRAM KONSELING REGULER PADA SISWA SDN 1 TOYA - Alfiani Nur Izzati; Andi Sulastri, Dr.Trianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe efforts to prevent bullying through regular counseling programs at SDN 1 Toya, identify the obstacles encountered, and find solutions to overcome them. The research uses a descriptive qualitative approach with research subjects including classroom teachers, Islamic Religious Education (PAI) teachers, psychology teachers, the school principal, and students. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results of the study show that prevention efforts are carried out through individual counseling, group counseling, and character-building workshops/training. The obstacles identified include limited time, lack of teacher understanding, students' low confidence to report incidents, and external environmental influences. Proposed solutions include teacher training, provision of comfortable counseling spaces, parent involvement, flexible scheduling, and ensuring confidentiality for student reporters. This study concludes that regular counseling programs can serve as an effective strategy for bullying prevention, even though the school does not yet have a dedicated school counselor.